Noise and quietness in Madrid parks (Spain): a GIS based environmental case analysis - Martínez Suárez, Pedro; Moreno Jiménez, Antonio (Anales de Geografía de la Universidad Complutense, 2013)
This research faces to analyze the environmental noise of Madrid urban parks, which should be rest and calm places in cities, due to the serious problem that noise means for citizens’ physical and mental health. With the aim of determining the pattern of noise levels in parks and analysing its relations with the sound sources, it is developed a method to describe the intensity and variability of noise in five parks, using GIS technology and statistical techniques applied to 2002 Acoustic Map of Madrid data. The findings display the high and sometimes unequal sound intensity in the parks of Madrid, and allow gauging its suitability for resting, recovering and enjoying.
Keywords: Environmental noise; urban parks; environmental quality; acoustic map; Madrid; GIS.